Rhodomyrtosone B, a membrane-targeting anti-MRSA natural acylgphloroglucinol from Rhodomyrtus tomentosa. (10th January 2019) - Zhao, Li-Yun; Liu, Hong-Xin; Wang, Lei; Xu, Zhi-Fang; Tan, Hai-Bo; Qiu, Sheng-Xiang
Abstract: Ethnopharmacological relevance: The leaves of Rhodomyrtus tomentosa are traditionally used in the treatment of infectious diseases such as wound infections in Chinese traditional medicine. The mechanisms of the activity of rhodomyrtosone B (RDSB), a natural acylphloroglucinol isolated from the leaves of Rhodomyrtus tomentosa, are still not understood. We provided a detailed investigation of the antibacterial action of RDSB against bacteria i n vitro and in vivo . Materials and methods: The antibacterial activity of RDSB was tested by the microdilution method against a panel of bacteria, and a time-killing assay was carried out according to CLSI guidelines. The cytotoxic potential of RDSB was evaluated against mammalian cells, and its haemolytic activity towards rabbit red blood cells (RBCs) was assessed. The mode of action of RDSB was investigated by targeting bacterial membranes, and its resistance was evaluated using a sequential passaging method. The antibacterial activities in vivo were assessed against MRSA in a mouse skin infection mode. Results: RDSB exhibited distinct antibacterial activities against selected Gram-positive pathogens responsible for serious infections, even including methicillin-resistant Staphylococcus aureus (MRSA) with a minimum inhibitory concentration (MIC) of 0.62–1.25 µg/mL and vancomycin-resistant Enterococcus faecium (VRE) with an MIC of 2.5 µg/mL. RDSB displayed much more rapid bactericidal activity against MRSA than that of vancomycin. The membrane-targeting experiments revealed that RDSB exhibited significant antibacterial activity with the perturbation of bacterial membrane potential and an increase in membrane permeability. In particular, RDSB had weak cytotoxicity to mammalian cells (IC50 >14 µg/mL) and has advantageous specificity against selected Gram-positive bacterial membranes rather than RBCs. Notably, RDSB displayed in vitro antibacterial activities against MRSA without drug-resistance and profoundly attenuated the skin ulcer formation in a murine model of MRSA infection under a single dose of 40 µg RDSB per mouse. Conclusion: RDSB has profound antibacterial activity against drug-resistant bacteria (MRSA and VRE) and low cytotoxicity. It is bactericidal in nature, and an increase in membrane permeability resulting from membrane perturbation is one of its modes of action. RDSB represents a promising natural antibiotic to combat drug-resistant (MRSA and VRE) infections. Graphical abstract: